Effect of Botanical Probiotic Containing Lactobacilli on Growth Performance and Populations of Bacteria in the Ceca, Cloaca, and Carcass Rinse of Broiler Chickens - Murry, A.C.; Jr; Hinton, A.; Jr; Buhr, R.J. (International Journal of Poultry Science, 2006)
This study was conducted to examine the effect of feeding a botanical probiotic (Feed Free™) containing Lactobacillus on growth performance of broiler chickens from 1 to 42 d of age. At 56 d, five broilers per pen were killed and processed to determine bacteria populations in the ceca, cloaca, and carcass rinse. The dietary treatments were the basal diet with coccidiostat and antibiotic (control), basal diet without coccidiostat and antibiotic (negative control) and basal diet supplemented with 0.10% probiotic. The results showed that body weights and average weight gain were not different (P > 0.05) due to treatment. Feed intake and feed to gain ratio from 22 to 42 d of age were lower (P < 0.001) for broilers fed 0.10% probiotic than broilers fed the control diets. The population of Lactobacilli recovered from cloaca contents was higher (P < 0.002) and the population of Clostridium perfringens recovered from cloaca contents was lower (P < 0.02) for broilers fed the 0.10% probiotic diet than for those fed the control diets. The population C. jejuni recovered from carcass rinses for broilers fed the diet supplemented with the probiotic tended (P < 0.11) to be lower when compared to the negative control. These results suggest that diets supplemented with the botanical probiotic containing Lactobacillus supports growth for broilers similar to the basal diet supplemented with antibiotic and coccidiostat, and with lower feed to gain ratio. Also, the botanical probiotic may reduce C. perfringens and C. jejuni in market-age broilers.